2022
DOI: 10.1086/718781
|View full text |Cite
|
Sign up to set email alerts
|

“Get Two Degrees for the Price of One”: Career Orientations and Choices of Double-Degree Students

Abstract: Double degrees have been identified in universities around the globe. The Colombian double degree is a local hybrid of the American double major and the local profession-enabling pregrado that universities, particularly elite private ones, marketize in a context of mass higher education, devaluation of first university degrees and a weak economy ensuing from social conflict. Through a narrative approach, we found that students learn to pursue two degrees to: maximize their investment in education; seek future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…, 2022). One recent study on the double major experience in Colombia found that students derive motivation to pursue multiple majors from a variety of sources, including job security, personal intellectual development and maximization of one's educational investment (Pineda et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022). One recent study on the double major experience in Colombia found that students derive motivation to pursue multiple majors from a variety of sources, including job security, personal intellectual development and maximization of one's educational investment (Pineda et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…During phase one of the larger research project, participants shared their academic experiences, resulting in the definition of themes related to multiple major motivations, advantages, disadvantages and awareness (Grabsch et al, 2022). One recent study on the double major experience in Colombia found that students derive motivation to pursue multiple majors from a variety of sources, including job security, personal intellectual development and maximization of one's educational investment (Pineda et al, 2022). By the same token, participants in a study on the Australian dual degree experience viewed their multiple majors as an advantage in terms of securing employment after graduation (Wimshurst and Manning, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…За допомогою наративного підходу було виявлено, що студенти здобувають два ступені, щоб максимізувати свої інвестиції в освіту, шукати майбутню гарантію роботи, з огляду на низьку цінність університетських повноважень і отримати визнання з боку однолітків і членів родини. Основний висновок полягає в тому, що студенти здобувають два ступені переважно через споживацькі орієнтації, які мають перевагу над освітнім обґрунтуванням [18].…”
unclassified